Polygamy on the Pedernales : Lyman Wight's Mormon villages in antebellum Texas, 1845 to 1858 - Johnson, Melvin C., 1949- (Utah State University Press, 2006)
Land Rights and the co-author of A Zuni Atlas, Hart originally wrote the manuscript in 1979 after a decade of historical work for Zuni Pueblo. He then set it aside but continued to pursue research about and for Zuni. Its publication, at last, inscribes an important contribution to Pueblo history and biography and a testimonial to a remarkable Native American leader.